2007
DOI: 10.1002/elan.200603837
|View full text |Cite
|
Sign up to set email alerts
|

Zeptomole Detection of Streptavidin Using Carbon Paste Electrode and Square‐Wave Voltammetry

Abstract: We compared the suitability of avidin and streptavidin for avidin-biotin technology in view of the sensitivity of the analysis using square-wave voltammetry. We found out during our preliminary experiments that streptavidin gave approximately 100 times higher electrochemical response in comparison with avidin at the same experimental conditions and concentration. Thus, we used two approaches for streptavidin determination -analysis directly in electrochemical cell and analysis by adsorptive transfer technique … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 33 publications
(11 citation statements)
references
References 43 publications
0
11
0
Order By: Relevance
“…The authors have shown that the method is specific, while its sensitivity is comparable to the electrophoretic methods developed for avidin determination in the transgenic plants. In another work [132] the authors have reported on ultra-sensitive detection of streptoavidin (from Streptomyces avidinii) in a zeptomolar concentrations by using carbon paste electrode.…”
Section: Analytical and Biochemical Applications Of Square-wave Voltamentioning
confidence: 99%
“…The authors have shown that the method is specific, while its sensitivity is comparable to the electrophoretic methods developed for avidin determination in the transgenic plants. In another work [132] the authors have reported on ultra-sensitive detection of streptoavidin (from Streptomyces avidinii) in a zeptomolar concentrations by using carbon paste electrode.…”
Section: Analytical and Biochemical Applications Of Square-wave Voltamentioning
confidence: 99%
“…SWV is one of the most sensitive electrochemical methods for analysis of biomolecules [8,18,20,21]. To prevent interferences [22] and to enable analysis of very low volumes [20,23], voltammetric methods can be coupled with adsorptive transfer stripping technique.…”
Section: Resultsmentioning
confidence: 99%
“…To prevent interferences [22] and to enable analysis of very low volumes [20,23], voltammetric methods can be coupled with adsorptive transfer stripping technique. The main improvement is based on electrode removing and rinsing after accumulating of target molecules [22,24].…”
Section: Resultsmentioning
confidence: 99%
“…The carbon paste was housed in a Teflon body having a 2.5 mm diameter of active disk surface. The electrode surface was polished before each determination with a soft filter paper prior to measurement [43-45]. For smoothing and baseline correction [46], the software GPES 4.4 was employed.…”
Section: Methodsmentioning
confidence: 99%